Littere baronum : the earliest cartulary of the counts of Champagne - Evergates, Theodore (Medieval Academy books, 2003)
This first edition of the cartulary contains 121 letters received from the barons and prelates of the county during the rule of Count Thibaut III (1198-1201) and the first decade of the regency of his widow, Countess Blanche (1201-22).